Soil conditions influence the advancement of first cork stripping in fertirrigated cork oaks - Camilo-Alves, Constança; Caldeira, Bento; Nunes, José António; Poeiras, Ana; Ribeiro, João; Maymone, Marta; Vaz, Margarida; Barroso, João Mota; Tlemcani, Mouhaydine; Almeida-Ribeiro, Nuno (Frontiers in Forests and Global Change, 2025)
IntroductionFertirrigation in cork oak plantations is a novel approach intended to accelerate growth until trees reach productive maturity, after which they are expected to be managed under rainfed conditions. This study investigated how site quality influenced the timing of the first stripping in a fertirrigated stand.MethodsREGASUBER is a 6-hectare experimental plot located in Coruche, Portugal, installed in 2014 with cork oaks planted with 4 × 4 spacing and subjected to four irrigation treatments. Trees height and diameter at breast height were annually measured, revealing the presence of two different site qualities, regular and inferior. Soil moisture was periodically monitored down to 1 meter deep at 10 locations per site. To access soil moisture at deeper layers, an exploratory electrical resistivity method was tested. The time to first stripping was modeled by irrigation treatment and site quality using nonlinear regression.ResultsTrees subjected to fertirrigation and located in regular site conditions showed the highest growth rates. Under these conditions, models predicted the first cork stripping at 13 to 15 years of age—about 10 years earlier than in rainfed trees on similar soils. Fertirrigation also contributed to more uniform growth across the stand, reducing uncertainty in stripping age. In inferior site conditions, fertirrigated trees were projected to reach the first stripping age between 20 and 25 years, which corresponds approximately to the age of rainfed trees in regular conditions. The resistivity method detected significantly higher soil moisture down to 4 meters in regular site quality, helping explain the observed growth differences.DiscussionThese results indicate that the benefits of fertirrigation for cork oak growth depend on soil water-holding capacity. Reliable methods to assess deep soil moisture are thus essential for forest managers considering this planting strategy.